ESTIMATING THE EFFICIENCY OF PROCUREMENTS OF STATE CUSTOMER THE REPUBLIC OF CRIMEA UNDER ITS REUNIFICATIONWITH THE RUSSIAN FEDERATION - T. V. Svishchuk; G. T. Gafurova (Russian Journal of Economics and Law)
Objective: to analyze the procurements of the executive authority of the Republic of Crimea in the transition period and to evaluate their effectiveness.Methods: the study used the methods of grouping, vertical and horizontal analysis, economic-mathematical modeling. Results: after the Republic of Crimea disconnection from the Ukraine and subsequent accession to the Russian Federation, the state customers in the region were in a difficult situation due to the adaptation of the existing procurement system to the Russian legislation norms. Basing on the data of the Republic of Crimea Ministry of Justice, the authors analyzed the state procurement across all stages of changing the legal field for the customers of the Republic. On the basis of the study, it is concluded that under the Ukrainian legislation the bulk of procurements was carried out without competitive procedures, while the remaining purchases showed the low level of savings. We also revealed the increase of procurement procedures complexity after the Republic accession to the Russian Federation, while during the transition period the customers made procurements according to a simplified procedure. The analysis of the procurement effectiveness for the customer showed that, as a result of legislative changes, the number and value of competitive procurements significantly increased, as well as the saving rate of tenders and auctions. On the basis of correlation-regression model the authors have proved the hypothesis that number of the procurement participants has an effect on the savings rate. As a result, the necessity of increasing the number of competitive procurements was substantiated, since the number of participants directly affects the savings rate in the course of bidding. Scientific novelty: on the basis of the analysis, the authors showed a positive economic effect from the changes in the legal framework of public procurement for a particular customer - the Republic of Crimea, which was manifested in the growth of savings rate and the number of competitive procedures. With economic-mathematical methods the authors proved the hypothesis that the saving rate increased following the results of procurement procedures, if the number of participants of the auctions and tenders increased. According to the results of the analysis, proposals for improving the contract procurement system are formulated. Practical significance: the proposed recommendations can be used by state customers and public authorities in procurement procedures and changes in laws and regulations in the field of public procurement with the aim of improving the efficiency of the contract system.